Patient perspectives on whole-genome sequencing for undiagnosed diseases. (January 2017) - Boeldt, Debra L; Cheung, Cynthia; Ariniello, Lauren; Darst, Burcu F; Topol, Sarah; Schork, Nicholas J; Philis-Tsimikas, Athena; Torkamani, Ali; Fortmann, Addie L; Bloss, Cinnamon S
This study assessed perspectives on whole-genome sequencing (WGS) for rare disease diagnosis and the process of receiving genetic results. Semistructured interviews were conducted with adult patients and parents of minor patients affected by idiopathic diseases (n = 10 cases). Three main themes were identified through qualitative data analysis and interpretation: perceived benefits of WGS; perceived drawbacks of WGS; and perceptions of the return of results from WGS. Findings suggest that patients and their families have important perspectives on the use of WGS in diagnostic odyssey cases. These perspectives could inform clinical sequencing research study designs as well as the appropriate deployment of patient and family support services in the context of clinical genome sequencing.